Development of Merdeka Curriculum’s Teaching Module as a Student-Centered Learning Plan Supported by E-learning Media - Muhammad Rasyid Ridho; Kiki Aryaningrum; Adrianus Dedy (Jurnal Ilmiah Profesi Pendidikan, 2025)
Teaching module is a learning plan document designed to guide teachers in carrying out daily instruction. Every teacher needs to have a well-structured learning plan to direct the learning process effectively and purposefully. Through this research, the researcher identified and described a teaching module based on Merdeka Curriculum as a learning plan that supports student-centered learning assisted by e-learning media. Student-centered learning is operationalized as a learning process that provides space for students to be more active in the learning process. The learning plan is designed using asynchronous e-learning media and Chromebook devices. A cooperative learning model was chosen as the main approach because it can accommodate elements of student-centered learning. The teaching module was developed with specifications consisting of general information components, core components, and appendices. Module validation was carried out by experts through assessments of quality and relevance, content structure, and language use. The validation results indicated a very high level of validity, with a score of 351 out of a maximum of 375, averaging 93.60% (categorized as very valid based on the Likert scale). The module was deemed feasible for use as a learning plan and was considered capable of facilitating student-centered learning. The follow-up to this research is the development of e-learning media in forms and specifications that align with the learning plans outlined in the teaching module.